Serial crystallography using automated drop dispensing. (22nd July 2021) - Su, Zhen; Cantlon, Joshua; Douthit, Lacey; Wiedorn, Max; Boutet, Sébastien; Kern, Jan; Yoon, Chun Hong; DePonte, Daniel
Abstract : The development of automated sample delivery and drop on demand methods is described. Abstract : Automated, pulsed liquid‐phase sample delivery has the potential to greatly improve the efficiency of both sample and photon use at pulsed X‐ray facilities. In this work, an automated drop on demand (DOD) system that accelerates sample exchange for serial femtosecond crystallography (SFX) is demonstrated. Four different protein crystal slurries were tested, and this technique is further improved here with an automatic sample‐cycling system whose effectiveness was verified by the indexing results. Here, high‐throughput SFX screening is shown to be possible at free‐electron laser facilities with very low risk of cross contamination and minimal downtime. The development of this technique will significantly reduce sample consumption and enable structure determination of proteins that are difficult to crystallize in large quantities. This work also lays the foundation for automating sample delivery.